O pojmowaniu praworządności socjalistycznej w Polsce Ludowej - Adam Lityński (Czasopismo Prawno-Historyczne)
The very essence of understanding the notion and meaning of law and order is the concept of law and the role assigned to it in a given state. Following the views of Marx and Engels, Vladimir IIich Ulyanov-Lenin saw law as an instrument of class domination. Such an interpretation of law had its logical consequence in the recognition that the state authority stood above the law, and that dictatorship was ‘nothing else but power limited by no constraints and bound by no laws’ (Lenin). A classical approach to law and order, however, did not apply in a situation when the power remained in the Bolsheviks’ hands.